The Effects of Sociodemographic Characteristics on Divorce Rates in Oman: Spatial Modeling of Marital Separations. Issue 3 (2nd July 2020) - Mansour, Shawky; Saleh, Emad; Al-Awadhi, Talal
Abstract : Divorce and family dissolution are global issues linked to various socioeconomic, demographic, and spatial variables. In the last decade, the divorce rate has increased dramatically across the Gulf Cooperation Council (GCC) states (Bahrain, Kuwait, Qatar, Oman, the United Arab Emirates, and Saudi Arabia). Rapid economic development, social transformation, and modernization have directly led to deep cultural changes in marriage and marital instability. Although the geographic perspectives of family formation and divorce risks have received considerable global attention, the spatial variations of divorce rates have not been examined across Arab countries or GCC communities. This study uses univariate and bivariate local indicators of spatial association (LISA) as well as Moran's I and spatial econometric regression models (spatial lag and spatial error) to examine the geographic distribution of divorce rates in Oman at a subnational level. Data sets from the 2010 census were used for the modeling and geospatial analysis and a range of statistical variables, including women's employment, female educational levels, urban residence, economically inactive females, and polygamous marriage, was examined. Spatial autocorrelation patterns and clusters of divorce rate associations were calculated and causal influences of sociodemographic characteristics on divorce were modeled. The findings revealed that the effects of sociodemographic variables on divorce and family instability across Omani subnational boundaries vary spatially. Hence, urban, suburban, and rural differences are significant predictors explaining the outcomes of family dissolution. There were high divorce rates, particularly in the northwest and northeast areas. Females' educational level was a negative predictor of divorce, whereas other variables were positively correlated with divorce rates. Although many global nonspatial studies have investigated divorce rates, there is a lack of research on family formation and dissolution in the Arab world and GCC states. This study fills the gap in the literature by contributing to the understanding of the role that the spatial structure of various sociodemographic variables plays in affecting divorce rates within local Omani communities.